The Effect of Tobacco Smoking on Adverse Events Following Adult Complex Deformity Surgery: Analysis of 270 Patients From the Prospective, Multicenter Scoli-RISK-1 Study. Issue 1 (1st January 2020) - Wilson, Jamie R.F.; Jiang, Fan; Badhiwala, Jetan H.; Shaffrey, Christopher I.; Carreon, Leah Y.; Cheung, Kenneth M.C.; Dahl, Benny T.; Ames, Christopher P.; Boachie-Adjei, Oheneba; Dekutoski, Mark B.; Lewis, Stephen J.; Matsuyama, Yukihiro; et al.
Abstract : Study Design: Post-hoc analysis of a prospective, multicenter cohort study. Objective: To analyze the impact of smoking on rates of postoperative adverse events (AEs) in patients undergoing high-risk adult spine deformity surgery. Summary of Background Data: Smoking is a known predictor of medical complications after adult deformity surgery, but the effect on complications, implant failure and other AEs has not been adequately described in prospective studies. Methods: Twenty-six patients with a history of current smoking were identified out of the 272 patients enrolled in the SCOLI-RISK-1 study who underwent complex adult spinal deformity surgery at 15 centers, with 2-year follow-up. The outcomes and incidence of AEs in these patients were compared to the nonsmoking cohort (n = 244) using univariate analysis, with additional multivariate regression to adjust for the effect of patient demographics, complexity of surgery, and other confounders. Results: The number of levels and complexity of surgery in both cohorts were comparable. In the univariate analysis, the rates of implant failure were almost double (odds ratio 2.28 [0.75–6.18]) in smoking group (n = 7; 26.9%)) that observed in the nonsmoking group (n = 34; 13.9%), but this was not statistically significant ( P  = 0.088). Surgery-related excessive bleeding (>4 L) was significantly higher in the smoking group (n = 5 vs . n = 9; 19.2% vs . 3.7%; OR 6.22[1.48 – 22.75]; P  = 0.006). Wound infection rates and respiratory complications were similar in both groups. In the multivariate analysis, the smoking group demonstrated a higher incidence of any surgery-related AEs over 2 years (n = 13 vs . n = 95; 50.0% vs . 38.9%; OR 2.12 [0.88–5.09]) ( P  = 0.094). Conclusion: In this secondary analysis of patients from the SCOLI-RISK-1 study, a history of smoking significantly increased the risk of excessive intraoperative bleeding and nonsignificantly increased the rate of implant failure or surgery-related AEs over 2 years. The authors therefore advocate a smoking cessation program in patients undergoing complex adult spine deformity surgery. Level of Evidence: 2 Abstract : A secondary analysis of the patients enrolled in the international, multicenter Scoli-RISK-1 study was performed. Smoking significantly increased the risk of perioperative excessive blood loss, and nonsignificantly increased the risk of implant failure rate and risk of adverse events over 2-year follow up.